Artificial Competence: The Impact of Generative AI Dependency on Students' Critical Thinking and Problem-Solving Agility - Kherismawati, Ni Putu Eka; Suandana, Ni Putu Widantari (PT.KARYA GEMAH RIPAH, 2025)
The integration of Generative AI (GenAI) like ChatGPT into academic environments has promised unprecedented efficiency. However, a growing concern arises regarding